Polemics around L. Štúr's essay 'Slavdom and the World of the Future': Romanticism and nihilism in the discourse of projects for the Slavic national revival in the 19th century - N.I. Nedashkovskaya; G.P. Myagkov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper addresses the polemics around the essay written by the famous Slovak public leader L. Štúr “Slavdom and the World of the Future” (Das Slawenthum und die Welt der Zukunft, 1851) presented against the background of methodological searches in the field of Slavic studies and history of social thought at the turn of the 19th and 20th centuries. By investigating into the history of creation, translation, and publication of the essay text in Russia in 1867 and 1909, the group of creators of the discourse around the projects for Slavic national revival has been specified. Through studying the review written by N.M. Petrovsky, the Slavicist from Kazan, for the second edition of the essay and published in Zhurnal Ministerstva Narodnogo Prosveshcheniya (“Journal of the Ministry of Education”) (1909), we have critically analyzed the source and the Pan-Slavic positions defended by the authors of the Russian translation, namely, the Academy fellow V.I. Lamanskii and his disciples K.Ya. Grot and T.D. Florinskii. Special attention has been paid to the methodological ideas and approaches that N.M. Petrovskii adopted to undertake the textual analysis and understand the mechanisms governing the ways various ideologemes of nationalism function.